Studi Komparatif Pembelajaran Tradisional dan Pembelajaran Berbasis AI terhadap Kemampuan Bernalar Siswa SMP - Nur Meizar, Syifa Azahra; Setiawati, Syifa Kamila; Rachman, Ichsan Fauzi (Jounal Nyanadassana, 2025)
Traditional learning often focuses on memorization and does not encourage students' critical thinking skills, while Artificial Intelligence (AI)-based learning offers a more interactive and adaptive approach. This research aims to compare the effectiveness of both methods in improving junior high school students' reasoning ability by using literature study method that analyzes various academic references related to traditional and AI-based learning. The results show that AI-based learning is more flexible, allows personalization of materials and increases student engagement in critical thinking, while traditional learning still excels in direct interaction, systematic delivery of concepts, and building social skills and student character. Integration of both methods can be an optimal solution to improve the quality of education by combining the advantages of each approach. A hybrid approach that combines AI-based learning and traditional methods can support an education system that is more adaptive, responsive to student needs, and able to provide a more comprehensive and effective learning experience. With a balanced learning strategy, students can be better prepared to face academic challenges and technological developments in the digital era.